Kekuatan Hukum Sertifikat Jaminan Fidusia yang didaftarkan Setelah Terjadinya Wanprestasi - I Gusti Ayu Dwi Meilaputri; Luh Putu Suryani; Pt. Gd. Seputra (Jurnal Analogi Hukum, 2019)
Fiduciary guarantee is a guarantee given in the form of a fiduciary. Where this has been arranged fiduciary guarantee in Fiduciary law. This own fiduciary guarantee facility have legal certainty against the parties involved in the fiduciary guarantee by bank credit to the public as a financial institution, where the debtor further directed by the bank to adjust its facilities credit given by the banks. This fiduciary itself has been regulated in the law on Fiduciary Guarantee that serves to help business activities. This journal discusses the fiduciary guarantee certificate that is registered by a financial institution after the tort, though there are rules concerning the grace period registration fiduciary guarantee so that later published the certificate of guarantee which has the force of law. This journal discusses the fiduciary guarantee certificate that is registered by a financial institution after the tort. This journal theme was chose because as time passes the human purposes and insufficient economic life needs are growing. The problem arises i.e. the law arising from fiduciary guarantee agreements and tort caused by the debtor. The method used is normative legislation and conceptual approach. The source of the legal materials in use are primary and secondary data sources. As for the analysis in the writing is done by holding the legal arguments based on inductive logic. The activities of the Bank with a fiduciary warranty is performed by holding the principle of trust. In the event of a tort committed by the debtor then the efforts taken by the Bank through late payment notifications via direct calls or provide a warning letter. If payment has not been made after the warning letter last attempt taken i.e. step completion by performing the execution of object fiduciary guarantee either through public auction or sales under the hand.